INVESTIGATING SIMPLE PAST TENSE SENTENCE ERRORS OF GRADE VIII STUDENTS AT SMP NEGERI 2 TINOMBO SELATAN - Aditiya, Popi; M. Said, Mawardin; Mashuri, Mashuri (e-Journal of ELTS (English Language Teaching Society), 2024)
The objectives of the research are to investigate and describe the students level of simple past tense and dificullties faced by Grade VIII Students SMP Negeri 2 Tinombo Selatan in Simple Past Tense. The research was conducted throught descriptive qualitative research design. Data analysis of the students Simple Past Tense on Regular and Iregular verb, It is found that the students level in Simple Past Tense is poor level since thay have limited knowledge english. In line with it, most of them understood the question, yet some of them found of dificcult to respomd to the questions immediatly. Furthermore, the problem faced by the students regarding simple past tense are lack vocabulary and regular Irregular verb. Problem of vocabulary was signified by the fact the students difficult answer the questions, and Regular Irregular verb problem in simple past tense was signified by the students difficult differences regular and irregular verb